Pengaruh Displin Dan Motivasi Terhadap Prestasi Kerja Pegawai Kementrian Keuangan Republik Indonesia Melalui Kepuasan Kerja - Pamungkas, Muhammad Akbar; Razak, Ismail; Silitonga, Eddy Sanusi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: 1) examine and analyze the influence of discipline and motivation on job satisfaction; 2) examine and analyze the influence of discipline and motivation on work performance; 3) examine and analyze the influence of job satisfaction on work performance; 4) examine and analyze the influence of discipline and motivation on employee work performance through job satisfaction. The research was conducted on employees of the Directorate General of Treasury, Ministry of Finance of the Republic of Indonesia. The sampling technique used was purposive sampling. The data analysis method employed descriptive analysis and path analysis. The results of the study indicate that: 1) there is a positive and significant influence of discipline and motivation on job satisfaction; 2) there is a positive and significant influence of discipline and motivation on work performance; 3) there is a positive and significant influence of job satisfaction on work performance; 4) there is a positive and significant influence of discipline and motivation on work performance through job satisfaction among employees of the Directorate General of Treasury, Ministry of Finance of the Republic of Indonesia.